Prenatal care from the perspective of the pregnant woman (Research, Society and Development, 2020)
Objective: describe the pregnant woman's perception of prenatal care. Methods: It is an exploratory study, with qualitative approach, carried out with 15 pregnant women in a Basic Health Unit located in the city of Manaus/AM. Results: after analyzing the information obtained, five thematic categories were constructed that describe the understanding of the pregnant woman about the importance of prenatal care, the performance of professionals in the prenatal consultation, the accessibility to the exams recommended by the Ministry of Health, education in the promotion of self-care, and adequate care from the perspective of the pregnant woman. Conclusion: the study revealed that in the face of the prenatal care they receive, pregnant women have the understanding that they are getting good care, emphasizing cordiality, active listening and ease of access as relevant factors for this understanding. However, the information extracted from the questionnaires suggests how much they are being neglected in the health services.